Management of adults and children undergoing chimeric antigen receptor T-cell therapy: best practice recommendations of the European Society for Blood and Marrow Transplantation (EBMT) and the Joint Accreditation Committee of ISCT and EBMT (JACIE) - Yakoub-Agha, Ibrahim; Chabannon, Christian; Bader, Peter; Basak, Grzegorz W.; Bonig, Halvard; Ciceri, Fabio; Corbacioglu, Selim; Duarte, Rafael F.; Einsele, Hermann; Hudecek, Michael; Kersten, Marie José; Köhl, Ulrike; et al. (Haematologica (Roma), 2020)
Chimeric antigen receptor (CAR) T cells are a novel class of anti-cancer therapy in which autologous or allogeneic T cells are engineered to express a CAR targeting a membrane antigen. In Europe, tisagenlecleucel (Kymriah™) is approved for the treatment of refractory/relapsed acute lymphoblastic leukemia in children and young adults as well as relapsed/refractory diffuse large B-cell lymphoma, while axicabtagene ciloleucel (Yescarta™) is approved for the treatment of relapsed/refractory high-grade B-cell lymphoma and primary mediastinal B-cell lymphoma. Both agents are genetically engineered autologous T cells targeting CD19. These practical recommendations, prepared under the auspices of the European Society of Blood and Marrow Transplantation, relate to patient care and supply chain management under the following headings: patient eligibility, screening laboratory tests and imaging and work-up prior to leukapheresis, how to perform leukapheresis, bridging therapy, lymphodepleting conditioning, product receipt and thawing, infusion of CAR T cells, short-term complications including cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome, antibiotic prophylaxis, medium-term complications including cytopenias and B-cell aplasia, nursing and psychological support for patients, long-term follow-up, post-authorization safety surveillance, and regulatory issues. These recommendations are not prescriptive and are intended as guidance in the use of this novel therapeutic class.